(untitled) (Journal of Laboratory Animal Science, 2018)
Experimental results of the hematological or biochemical data are best interpreted and compared based on previously reported baseline data for the strains in question. Maintenance and managemental conditions of the animals varies from organization to organization. Naturally, the baseline data for hematology and biochemistry may vary amongst the same species or strains of animals. This study was undertaken to establish hematological reference values in mice and rat strains maintained at Advanced Centre for Treatment, Research and Education in Cancer (ACTREC), Navi Mumbai and to compare with that of the values reported by other workers as in the literature. Hematological values were found to be within the normal range when compared to the values reported in the literature. Slight deviations in these values have been noticed within the strain. However, they remain within the reported normal range. Most of the time, the normal range values were so wide that it necessitates the need for the laboratory-specific baseline data. The wide range may be the result of genetic changes, change in feed, housing conditions, technique and equipments used or management conditions. The hematological values of these strains may provide valuable baseline data to the researchers for future experiments using these inbred strains.